Impact of air pollution on the health of the older adults during physical activity and sedentary behavior: A systematic review - D'Oliveira A.* (2023)
© 2023 Elsevier Inc.Background: Air pollution, in addition to presenting health risks, can impact the practice of physical activity (PA) and sedentary behavior (SB) in older adults. This study analyzed the impact of air pollution on the health of older adults during PA and SB, through a systematic review. Methods: A keyword and reference search was performed in PubMed, SCOPUS, SPORTDiscus, and Web of Science. Predetermined selection criteria included study designs: interventions or experiments, retrospective or prospective cohort studies, cross-sectional studies and case-control studies; population: older adults aged 60 years or older; exposures: specific air pollutants (particulate matter (PM), nitrogen dioxide (NO2), ozone (O3), carbon monoxide (CO), sulfur dioxide (SO2), black carbon (CN), ultrafine particles (PU), nitrogen oxides (NOx) and biomass fuels) indoors and outdoors; and outcomes: physical activity and/or sedentary behavior. Results: The beneficial effects of PA were attenuated or harmed in 11 studies, showing negative impacts on the health of the older adults, mainly by PM2.5 pollutants. On the other hand, in 10 studies the effects of PA were greater than the negative effects of air pollutants, with a greater frequency in relation to PM2.5. In general, even the articles presenting controversial results suggest that practicing PA in polluted environments is more favorable to the health of older adults than remaining in SB. Discussion and conclusions: On the one hand, air pollution negatively impacted the health of the older adults during PA practices, while on the other hand, PA can mitigate the negative effects of pollutants on the health of older adults during the practices. Evidence shows that practicing PA in environments with low concentrations of pollutants can provide gains and reduce health risks. Remaining in SB in environments with high levels of air pollution worsens the health of older adults.